2008
DOI: 10.1097/mlr.0b013e3181653d58
|View full text |Cite
|
Sign up to set email alerts
|

Physician Implicit Attitudes and Stereotypes About Race and Quality of Medical Care

Abstract: Pediatricians held less implicit race bias compared with other MDs and others in society. Among pediatricians we found evidence of a moderate implicit "perceived patient compliance and race" stereotype. Further research is needed to explore whether physician implicit attitudes and stereotypes about race predict quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
246
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(259 citation statements)
references
References 32 publications
10
246
3
Order By: Relevance
“…A widely cited report by Green and colleagues 13 found that resident clinicians with greater implicit bias were less likely to recommend thrombolytic therapy for a hypothetical black patient with myocardial infarction, but this did not occur when the patient was described as white. On the other hand, a study 18,19 on pediatric decision-making showed that some of the hypothetical decisions were associated with implicit bias, but others were not. Finally, a study 20 with medical students failed to find any relation between hypothetical clinical decisions and the students' implicit bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A widely cited report by Green and colleagues 13 found that resident clinicians with greater implicit bias were less likely to recommend thrombolytic therapy for a hypothetical black patient with myocardial infarction, but this did not occur when the patient was described as white. On the other hand, a study 18,19 on pediatric decision-making showed that some of the hypothetical decisions were associated with implicit bias, but others were not. Finally, a study 20 with medical students failed to find any relation between hypothetical clinical decisions and the students' implicit bias.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Evidence on the effects of clinician implicit bias on medical decisions in hypothetical scenarios has been mixed. 13,[18][19][20] The linkage between clinician implicit bias and more technical processes and outcomes of care has not been Electronic supplementary material The online version of this article (doi:10.1007/s11606-014-2795-z) contains supplementary material, which is available to authorized users. directly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Green and colleagues 45 found that resident clinicians with greater implicit bias were less likely to recommend thrombolytic therapy for a hypothetical black patient with myocardial infarction, but this did not occur when the patient was described as white. On the other hand, research on pediatric decision making 49,50 showed that some hypothetical decisions were associated with implicit bias but others were not. However, a study 51 with medical students failed to find any relation between clinical decisions in the hypothetical scenarios and the students' implicit bias.…”
Section: Race/ethnicity Racism and Cvdmentioning
confidence: 99%
“…7 Although Sabin et al found less implicit race bias among pediatricians compared with other physicians, implicit (but not explicit) bias was still present, linking compliance with being White. 26 Sabin et al also examined implicit race bias in physicians as a whole using data from Harvard's Project Implicit© website, which allows volunteers to take various versions of the IAT online. 27 Overall, the 2,535 website participants who reported having an MD degree showed significant pro-White bias.…”
Section: Physicians and Implicit Biasmentioning
confidence: 99%